2006
DOI: 10.1007/s11284-006-0194-6
|View full text |Cite
|
Sign up to set email alerts
|

Soil nutrient status after bamboo flowering and death in a seasonal tropical forest in western Thailand

Abstract: We have examined the surface (0-10 cm) soil characteristics of sites after bamboo (Cephalostachyum pergracile) mass flowering and death (DB sites) in comparison with sites with living bamboo (Bambusa tulda) (LB sites) in a seasonal tropical forest in Thailand.One year after bamboo flowering the DB sites were acidic with lower concentrations of exchangeable Ca and Mg and soil nitrogen than the LB sites. Therefore, although leaf and root litter of the dead bamboo was deposited in the DB sites after bamboo flower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 10 publications
4
21
0
Order By: Relevance
“…During rainy season, AA stand showed the highest MBN contents. The seasonal pattern of soil respiration rates with high and low rates in hot-rainy season and cool-dry season, respectively, was in accordance with other observation in Thailand (Hashimoto et al 2004, Takahashi et al 2007 or other tropical seasonal forests (Cleveland et al 2004, Liu et al 2012). Soil respiration is often explained as a function of temperature (Ishizuka et al 2006), and soil water content is also suggested to play an important role in tropical soils where less inter-seasonal variability in temperature are observed (Hashimoto 2005, Takahashi et al 2009).…”
Section: Resultssupporting
confidence: 90%
“…During rainy season, AA stand showed the highest MBN contents. The seasonal pattern of soil respiration rates with high and low rates in hot-rainy season and cool-dry season, respectively, was in accordance with other observation in Thailand (Hashimoto et al 2004, Takahashi et al 2007 or other tropical seasonal forests (Cleveland et al 2004, Liu et al 2012). Soil respiration is often explained as a function of temperature (Ishizuka et al 2006), and soil water content is also suggested to play an important role in tropical soils where less inter-seasonal variability in temperature are observed (Hashimoto 2005, Takahashi et al 2009).…”
Section: Resultssupporting
confidence: 90%
“…Soil is classified as Alfisols 19 derived from sedimentary rock, gneiss and limestone. Undergrowth bamboo also influences surface soil conditions at the sites 22 . Soil properties in the teak plantation (T-Y plot, see below) are shown in Table 1.…”
Section: Sitesmentioning
confidence: 99%
“…Decomposition of accumulated organic matters resulted in increasing soil organic carbons. Post-flowering and Flowering sites accumulated higher quantity of organic matters especially in these gregarious flowering instances that could be gradually incorporated with soil organic pools (Takahashi et al 2007). On the other hand, organic carbon recorded in pre-flowering sites could be an optimum quantity for the maintenance of their ecosystem, although, factors such as loading of dry leaves, twigs, branches and culms from dying bamboo lead to increase soil organic carbon after initiation of gregarious flowering in bamboo forest.…”
Section: Resultsmentioning
confidence: 99%
“…In gregarious flowering, all members of the cohorts enter the reproductive phase approximately at the same time and after flowering and seeding, the parents die en mass (Tewari 1992, John andMascarenhas 1994). Gregarious flowering of bamboo alarms different magnitude of impacts, be it socio-economic or environmental issues; it causes drastic change in forest ecosystem and environmental conditions including decline of soil nutrient pool and microbial population (Chauhan and Saxena 1985, Marod et al 2002, Takahashi et al 2007, Rai 2009). Nutrient uptake by the bamboo ceases after the completion of mass flowering and fruiting huge quantity of dry matter are deposited in the forest (Takahashi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation